The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1997
DOI: 10.1590/s0100-879x1997000800003
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D receptor alleles and bone mineral density in a normal premenopausal Brazilian female population

Abstract: Studies on the association between vitamin D receptor (VDR) polymorphism and bone mineral density (BMD) in different populations have produced conflicting results probably due to ethnic differences in the populations studied. The Brazilian population is characterized by a very broad genetic background and a high degree of miscegenation. Of an initial group of 164, we studied 127 women from the city of São Paulo, aged 20 to 47 years (median, 31 years), with normal menses, a normal diet and no history of disease… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
13
1
1

Year Published

1998
1998
2015
2015

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 10 publications
(9 reference statements)
6
13
1
1
Order By: Relevance
“…In agreement with this fact, we did not detect any BB genotype in the 6 individuals of oriental extraction who participated in the present study. Although the number of subjects involved is small, these data agree with those observed in another study conducted on a population of premenopausal women in the city of São Paulo (9), where the B allele was found only in 16.6% of orientals, in contrast to 60.8% of whites and 74.9% of blacks and crossbreds.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…In agreement with this fact, we did not detect any BB genotype in the 6 individuals of oriental extraction who participated in the present study. Although the number of subjects involved is small, these data agree with those observed in another study conducted on a population of premenopausal women in the city of São Paulo (9), where the B allele was found only in 16.6% of orientals, in contrast to 60.8% of whites and 74.9% of blacks and crossbreds.…”
Section: Discussionsupporting
confidence: 89%
“…Morrison et al (5) suggested that the alleles of the vitamin D receptor (VDR) may be of high predictive value in the quantification of bone mass in an individual. Although later studies conducted on different racial groups in different countries have produced conflicting results (6-8), we observed the same correlation as that reported by Morrison et al in a population of 126 premenopausal Brazilian women from the city of São Paulo (9). We reported that a group of women with a BB genotype had, on average, a lower bone mineral density (BMD) than women with the bb genotype and this difference was more significant in a region of the neck of the femur.…”
Section: Introductionsupporting
confidence: 90%
“…We first attempted to study the association between vitamin D receptor polymorphism and BMD in a similar population. Lazaretti-Castro et al (27) investigated vitamin D receptor gene polymorphism and BMD in a population of young women from the city of São Paulo and detected lower spinal and femoral BMD in subjects with the BB genotype when compared with the bb genotype.…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies have been published over the last 3 years; some were affirmative, in the sense that they described an association between VDR genotypes and BMD, risk of fractures or rates of bone loss [60, 61, 62, 63, 64, 65, 66, 67, 68, 69, 70, 71, 72, 73, 74, 75, 76, 77], whereas others did not [56, 57, 78, 79, 80, 81, 82, 83, 84, 85, 86, 87, 88, 89, 90, 91, 92, 93, 94, 95]. The subject has been debated and revised [18, 19, 20, 21, 22, 23, 24, 25, 96, 97, 98, 99, 100, 101, 102].…”
Section: Vitamin D Receptor Genementioning
confidence: 99%